2019
DOI: 10.2147/ijgm.s205506
|View full text |Cite
|
Sign up to set email alerts
|

<p>High sensitivity C-reactive protein as a predictive of intima-media thickness in patients with end-stage renal disease on regular hemodialysis</p>

Abstract: Background Several emerging problems of regular hemodialysis (HD) including cardiovascular complication or atherosclerosis formation caused by chronic inflammation. Intima-media thickness (IMT) of the carotid artery can be applied as a marker of atherosclerosis progression. This study was designed to identify the predictive of IMT progression among end-stage renal disease (ESRD) subject. Methods This cohort study was performed at the Hemodialysis Unit of Dr. Kariadi Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…46 The malnutrition–inflammation–atherosclerosis complex proposes inflammation as a link between malnutrition and CV disease during maintenance dialysis. 47 In contrast to observations made in adults, 31 C-reactive protein as a marker of inflammation did not influence IMT during dialysis in our investigation. Evaluation of other markers for inflammation, like interleukin 6 and tumor necrosis factor-alpha, 47 seems warranted but is not available in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…46 The malnutrition–inflammation–atherosclerosis complex proposes inflammation as a link between malnutrition and CV disease during maintenance dialysis. 47 In contrast to observations made in adults, 31 C-reactive protein as a marker of inflammation did not influence IMT during dialysis in our investigation. Evaluation of other markers for inflammation, like interleukin 6 and tumor necrosis factor-alpha, 47 seems warranted but is not available in our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Systolic BP, 14 low-density lipoprotein cholesterol, 27 and body mass index (BMI) 14 are known to broadly impact IMT in health as well as disease and were therefore used in all submodels. Serum phosphorous, 28 bicarbonate, 29 serum albumin, 30 and C-reactive protein 31 were only assessed during dialysis. Kidney function 32 and immunosuppressive medication 33 were only incorporated into the separate models for late and preemptive KTx, whereas time on dialysis (dialysis vintage) was only included for late KTx.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various experimental studies highlighted the mechanisms by which phosphate in excess may adversely affect the cardiovascular system [ 21 , 22 ]. Thus, it may directly contribute to vascular damage by pro-inflammatory actions on the vascular smooth muscle cell leading to endothelial dysfunction and promoting vascular calcification [ 23 , 24 ]. Furthermore, a high dietary phosphate content may contribute to atherogenesis [ 25 ] and has also been linked to a more rapid progression of CKD to ESKD [ 19 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is involved in the process of end-stage renal disease (ESRD) mainly caused by diabetic nephropathy and chronic glomerulonephritis [1][2][3]. Our previous study and others showed that inflammatory marker is a significant predictor of intima-media thickness (IMT) progression and increased IMT had poor survival in ESRD patients [4][5][6]. It has been reported that increased IMT, as a strong predictor of cardiovascular disease and mortality, was associated with inflammation even in non-dialysis patients [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study and others showed that inflammatory marker is a significant predictor of intima-media thickness (IMT) progression and increased IMT had poor survival in ESRD patients [ 4 6 ]. It has been reported that increased IMT, as a strong predictor of cardiovascular disease and mortality, was associated with inflammation even in non-dialysis patients [ 5 , 7 ]. Thus, it is important to pay attention to inflammation in ESRD as well as non-dialysis patients.…”
Section: Introductionmentioning
confidence: 99%